2004
DOI: 10.1353/npj.2005.0001
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Revegetation in Arizona's Hot Desert: The Advantages of Container Stock

Abstract: We found that the most effective and economical method for establishing native shrubs on extensive areas of retired cropland in southern Arizona makes use of drip irrigation and 3.8-l (1-gal) transplants (outplants). In March 2001, we established a small (8 ha [20 ac]) field trial to test the effectiveness of different combinations of transplanting, seeding, drip irrigation, and furrow irrigation. Treatments utilizing transplants and drip irrigation had higher survival and lower densities of weed species than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…ex Griffiths (blue grama) was low after 2.5 years, at only 18% and 28%, respectively. These and other studies indicate that revegetation effectiveness can sharply vary depending on method (seeding versus planting), species, and treatment (e.g., irrigation or cages to provide herbivory protection) used for revegetation (Roundy et al 2001;Bean et al 2004;Abella and Newton 2009). No well-established protocols exist for revegetating planned or unplanned disturbances in deserts, and financial cost projections for accomplishing revegetation are rare.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…ex Griffiths (blue grama) was low after 2.5 years, at only 18% and 28%, respectively. These and other studies indicate that revegetation effectiveness can sharply vary depending on method (seeding versus planting), species, and treatment (e.g., irrigation or cages to provide herbivory protection) used for revegetation (Roundy et al 2001;Bean et al 2004;Abella and Newton 2009). No well-established protocols exist for revegetating planned or unplanned disturbances in deserts, and financial cost projections for accomplishing revegetation are rare.…”
Section: Introductionmentioning
confidence: 84%
“…For example, included 28 species in their seed mix, with 14 species established by one year after seeding and only five species occupying ≥50% of 10-m 2 plots three years after seeding. Other seeding studies in the Sonoran Desert have reported no (Bainbridge and Virginia 1990;Woods et al 2012) or minimal plant establishment (Bean et al 2004), or have noted limited establishment based on retrospectively measuring plant community composition of seeded sites (Judd and Judd 1976;Jackson et al 1991;Banerjee et al 2006). The next most species-rich outplanting study in the Sonoran Desert, Bean et al (2004), reported that at least six species of shrubs and grasses exhibited ≥69% one-year survival on derelict farmland.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The volcanic cinder soils on which this trial was conducted are among the driest in the Flagstaff area, with a 0 to 15 cm gravimetric soil moisture content of less than 2% in early summer (Abella and Covington 2006). We did not provide any supplemental water to outplants, and irrigation (where practical) or slow-release irrigation (such as DriWater) may be especially important for outplants on these dry soils (Newton 2001, Bean et al 2004). Another consideration is that plants were five months old and 10 cm tall on average at the time of planting.…”
Section: Survival Patternsmentioning
confidence: 99%